POLA ASUH ORANGTUA MEMPENGARUHI KEJADIAN SCHOOL REFUSAL PADA ANAK USIA TODDLER DI PAUD DARUL HIKMAH MOJOSANTREN KECEMATAN KRIAN SIDOARJO - Hana Putri Rahmaniah; Nur Hidaayah (Jurnal Ilmiah Kesehatan, 2014)
School refusal is influenced from various factors, including the parents' parenting. Not all children feel that the school is a time of fun. This study aims to determine the relationship between parenting parents with the incident toddler School refusal in children in early childhood Darul Hikmah Mojosantren Krian Sidoarjo. Using a case control study design with a retrospective approach is that parents in early childhood population Darul Hikmah Mojosantren Krian Sidoarjo. Samples were taken using simple random sampling technique a total of 32 respondents. Independent variables are parenting a parent, while the dependent variable was the incidence School refusal. Retrieval of data using a questionnaire and analyzed using chi-square test with significance level α=0.05. The results showed that of 18 respondents to comply with parenting, is almost entirely (88.8%) had events School refusal. The results of chi-square test and are not eligible to use the Fisher exact a (a = 0.001<0.05) means that there is a relationship between parenting parents with School refusal in early childhood events Darul Hikmah Mojosantren Krian Sidoarjo. Research conclusions if the pattern of care is given to the child's parents is good, then the child will not suffer School refusal. Provision of information about good parenting and about the School refusal symptoms, so parents can be aware of the incident.